2015
DOI: 10.1007/s00134-015-3898-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluid administration on arterial load in septic shock patients

Abstract: Fluid administration significantly reduced arterial load in critically patients with septic shock and acute circulatory failure, even when increasing cardiac output. This explains why some septic patients increase their cardiac output after fluid administration without improving blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 36 publications
4
57
1
1
Order By: Relevance
“…Conversely, the pH‐lowering effects of saline may lead to higher doses of vasopressors for longer durations compared with balanced fluid resuscitation . Over‐resuscitation with fluids was also found to decrease the systemic vascular resistance, negating the intended therapeutic effect of the fluid or vasopressor used . Hydrocortisone may also interact with the fluid compartments; pretreatment with this agent was shown to preserve glycocalyx integrity in both septic animal models and pilot surgical studies .…”
Section: Fluid Pharmacokinetics and Pharmacodynamics In The Septic Pamentioning
confidence: 99%
“…Conversely, the pH‐lowering effects of saline may lead to higher doses of vasopressors for longer durations compared with balanced fluid resuscitation . Over‐resuscitation with fluids was also found to decrease the systemic vascular resistance, negating the intended therapeutic effect of the fluid or vasopressor used . Hydrocortisone may also interact with the fluid compartments; pretreatment with this agent was shown to preserve glycocalyx integrity in both septic animal models and pilot surgical studies .…”
Section: Fluid Pharmacokinetics and Pharmacodynamics In The Septic Pamentioning
confidence: 99%
“…Monge-Garcia et al administered 500 mL of either crystalloid or colloid for 30 min and evaluated the SV/CO using Doppler transesophageal echocardiography and reported a 10% decrease in the SVR by infusion in fluid responders (67%) [10]. This result suggests that not only increased preload but also decreased afterload is involved in the increase of SV/CO with small amounts of fluid challenge.…”
Section: Reviewmentioning
confidence: 99%
“…Conditions are consistent with blood pressure control for critically ill patients, who have sepsis or ARDS. SVR is also known to decrease by infusion in septic patients [10]. Furthermore, in septic patients, although the MAP is transiently increased by the fluid bolus administration, it returns to base line within 1 h [8, 9].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have shown that only approximately 50% of critically ill patients in whom the fluid is administered do exhibit an increase in blood flow and that half of the patients will receive unnecessary fluid loading. [4567891011]…”
Section: Introductionmentioning
confidence: 99%